A BalanÃa Comercial do Nordeste Brasileiro: Uma AnÃlise EmpÃrica - Mariana Gomes de Freitas Damasceno (2003)
This dissertation is a presentation of practical studies based on statistics and other data of the International Trade Balance, imports and exports of North-East Region of Brazil --of which the three most import states are Bahia, CearÃ and Pernambuco--, and of national economic from 1990 through 2001. The figures of foreign commerce of each individual state, of the whole region, and of the country as a whole, are measured and compared. The grade of openness of each of these economies is revealed. Through the method of Ordinary Minimum Squares (OMM) an estimate is made of the past impact of internal variables like price (exchange rates), local revenues (industrial production and ICMS), and external revenues (the USA index of Industrial Product and GNP) on the regionâs ability to augment the volume of exports and imports.